Potential Infiltration Determination in Areas of Influence of the Zona Bananera Aquifer in Northern Colombia (2020)
Through the implementation of geographic information systems (GIS) and images of the study area obtained by remote sensors, the curve number method (NC) was implemented in this research, in order to determine potential recharge zones in two micro-basins in the aquifer region called Zona Bananera, located in the department of Magdalena in Northern Colombia. Potential infiltration of the area was estimated and the hydrological response for precipitation events with different return periods was evaluated. The predominant hydrological soil groups were found to be A and B, with 77.4% (84115.2 ha) in the Sevilla River micro-basin and 81.6% (7466.1 ha) in La Aguja micro-basin. The Sevilla River micro-basin showed both the best water regulation and enhancement of the infiltration process, evidenced by the existence of low as well as medium values ​​of curve number and potential surface runoff. The highest values ​​of potential runoff were in the middle and lower part of the micro-basins, where there are extensive areas covered with banana crops; indicating that anthropic intervention is a determining factor in the area’s hydrological response. Under current conditions, the micro-basins show a minimal risk of erosive processes for rainfall with return periods of less than 5 years, due to runoff occurrence of less than 100 mm. Within the study area, it was found that approximately 3380 hectares show favorable conditions to contribute to the recharge of the Zona Bananera aquifer, making it a strategic conservation area.